Topological Indices of Derived Networks of Benzene Ring Embedded in P-Type Surface on 2 D - Feng Yin; Muhammad Numan; Saad Ihsan Butt; Adnan Aslam; Andleeb Kausar (Journal of Chemistry)
Topological index (TI) is a numerical number assigned to the molecular structure that is used for correlation analysis in pharmacology, toxicology, and theoretical and environmental chemistry. Benzene ring embedded in the P-type surface on 2 D network has stability similar to C60 and can be defined as 3 D linkage of C8 rings. This structure is the simplest possible tilling of the periodic minimal surface P which contains one type of carbon atom. In this paper, we compute general Randić, general Zagreb, general sum-connectivity, first Zagreb, second Zagreb, and ABC and GA indices of two operations (simple medial and stellation) of 2 D network of benzene ring. Also, the exact expressions of ABC4 and GA5 indices of these structures are computed.